Challenges and strategies towards copper-based catalysts for enhanced electrochemical CO2 reduction to multi-carbon products. (15th January 2023) - Sun, Bo; Dai, Mingwei; Cai, Songchi; Cheng, Haoyan; Song, Kexing; Yu, Ying; Hu, Hao
Highlights: Recent Cu-based catalysts for CO2 reduction to C2+ products are summarized. Mechanism of CO2 RR on Cu surfaces are elaborated separately. Recent approaches to catalyst design are summarized. Challenges and outlooks in Cu-based catalysts towards CO2 RR are highlighted. Abstract: Electrochemical CO2 reduction (CO2 RR) driven by renewable energy is a promising strategy to close the anthropogenic chemical carbon cycle and simultaneously increase carbon feedstock production. Multi-carbon (C2+ ) products from CO2 RR are very attractive as they are important fuels, chemicals, and industrial raw materials. Copper has received wide attention as an excellent metal catalyst for the formation of C2+ products through CO2 RR. Although important advances have been made for Cu-based catalysts to produce C2+ products, there are still challenges such as wide product diversity, poor yield, and high overpotentials. The structure and composition of catalysts affect the binding strength of key intermediates such as *CO and *OCCO during the CO2 RR process. Therefore, it is necessary to have in-depth knowledge of the relationship between the structural components and performance to figure out reasonable design strategies. Here, we summarize the favored mechanisms for CO2 RR and the possible pathways to produce C2+ products on the surfaces of Cu-based materials. Recent approaches to catalyst design, including structure control, oxide-derived Cu, bimetallic strategy, surface modification, and atomic-level dispersion, are evaluated for their CO2 RR performance. Finally, challenges and perspectives in this field are highlighted for further improvement of CO2 RR.